2009
DOI: 10.1787/224422031753
|View full text |Cite
|
Sign up to set email alerts
|

Extensive Margins in Agriculture

Abstract: This paper examines whether the growth in agricultural trade of 69 countries between 1996 and 2006 has taken place at the intensive or the extensive margin. The paper addresses the questions: have agricultural exports during this period expanded more through the intensive margin (more exports of established goods to traditional partners) or through the extensive margin (new trade flows in new products and/or to new partners)? At the intensive margin, do richer countries export greater volumes, or do they recei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 6 publications
0
6
1
Order By: Relevance
“…That is, 29% of the additional exports by richer countries are at the extensive margin (more items to more markets) while more than 70% is from higher volumes of the items exported (Table 22 first column). This result differs from those of HK who found that most of merchandise trade of richer countries is at the extensive margin and from Liapis (2009) where for 2006, exports of agricultural products by richer countries, (as opposed to only processed proucts) was mostly at the extensive margin.…”
Section: Resultscontrasting
confidence: 92%
See 4 more Smart Citations
“…That is, 29% of the additional exports by richer countries are at the extensive margin (more items to more markets) while more than 70% is from higher volumes of the items exported (Table 22 first column). This result differs from those of HK who found that most of merchandise trade of richer countries is at the extensive margin and from Liapis (2009) where for 2006, exports of agricultural products by richer countries, (as opposed to only processed proucts) was mostly at the extensive margin.…”
Section: Resultscontrasting
confidence: 92%
“…22 In addition, we examine the impact of trade facilitation variables in exporting goods on the respective margins. Previous OECD work Liapis (2009) used similar methodology on all agricultural goods. In this report, the focus is on processed products.…”
Section: Intensive and Extensive Margin Of Processed Productsmentioning
confidence: 99%
See 3 more Smart Citations